PEREMPUAN PAPUA DAN PELUANG POLITIK DI ERA OTSUS PAPUA - Muridan Satrio Widjojo (Masyarakat Indonesia, 2012)
This paper discusses the condition and the dynamics of Papuan womenspoliticalparticipationin the reformation and democratization era. Traditionally, women arepositioned as subordinate of men.This paperargues that there are increasing opportunities for womens participation in the decision making process. Based on Papuan historical experiences, the traditionalsocial construction has been enriched by educationand modern bureaucracy introduced by the churches, the Dutch colonial governmentand the Indonesian government. In some cases, the rise of Papuan womens politicalparticipation is facilitated by family. Since the late 1980s civil society movement,the establishment of a number of NGOs has grown significantly and provided moreopportunities for women activists. Women empowerment by this group is not onlydriven by individual motivation but also supportedby family condition and the newpolitical context. Significant progress of position and roles as well as the new politicalspace for women has been translatedinto the new creation of women seat within thestructure of Papuan People Assembly (MRP). This is seen as a milestone in the historyof women movement in Papua. Considering the strategic role and position of womenspecifically in MRP and in Papuan political dynamic, women leaders in Papuaareexpected to contribute more toward conflict resolution.Keywords: papuan women, women empowerment, women movement, MRP